Influence of Vertical Geometric Irregularity on the Seismic Response of High-Rise Buildings Equipped with Base Isolation System - Olivera Perez, Romel Moises (2024)
In the year 2022 according to the United Nations, the world population is three times larger than the twentieth century, which affects the demand for land and consequently the cost per m2 increases. Likewise, it requires occupants to choose to build high-rise buildings to maximize the area acquired, consequently most structures require huge shear walls that increase the cost in steel, and in turn reduce the profitability of real estate for lack of aesthetic spaces on the floors. Now, recent architectural models do not allow regular structures, consequently, different irregularities occur. The present work develops the influence of vertical geometric irregularity in high-rise buildings with base isolation system, by which the researchers, modellers and designers, carried out the analysis of a regular pattern model (MPAT) based on shear walls, columns and beams against 12 different models, presented in their structural configuration different vertical geometric irregularities, consisting of 20 floors. It was analyzed by means of the seismic properties established in the Peruvian regulation of buildings norm E.030 and E0.31, providing with rigidity, resistance, ductility to the structure, likewise the elements of isolation of base of the type Elastomeric LRB and Slider were placed, which were developed with a nonlinear analysis time history with a total of 7 pairs of seismic registrations. Finally, it was observed in the displacement analysis that the irregular structures compared to the regular structure do not present a variation greater than 3.14%. Similarly, drifts between floors were analysed in which the models M1T3, M2T3, M3T3, and M4T3 presented greater drifts compared to the regular model, obtaining in the model M4T3 an increase in the drift of 56. 74%. On the other hand, in the accelerations per level, the M2T3 model obtained an increase of 60.63% compared to the standard model. Finally in the analysis of energy dissipation with seismic isolators, the M4T3 model dissipates 92.84% of energy generated in the structure, consequently the seismic effect is dissipated directly by the base isolators.